An Integrated Approach For Fatigue Life Estimation Based On Continuum Mechanics Theory And Genetic Algorithm - M., Kamal; M. M., Rahman (Universiti Malaysia Pahang, 2015)
This paper presents the performance analysis of a newly proposed fatigue estimation model. Research for fatigue estimation methods is focused on developing the capability to handle complex multiaxial loading conditions. This study focuses on an attempt to develop a new fatigue life estimation model using the concepts of continuum mechanics with a critical plane based approach. A genetic algorithm is utilized to estimate the coefficients of stress and strain components. Experimental data for fatigue lives for EN3B steel alloy for in-phase and out-of-phase loading conditions are used to calibrate and analyze the accuracy of the proposed model. Finite element analysis is used to determine an experimental fatigue life of EN3B steel alloy published in literature for validation. The proposed model is easy to implement and does not require the determination of new material constants and material properties. Fatigue life prediction from the proposed model shows good agreement with published results for in-phase and out-of-phase multiaxial loading